Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300888
|View full text |Cite
|
Sign up to set email alerts
|

As Light as You Aspire to Be

Abstract: Supporting exercise adherence through technology remains an important HCI challenge. Recent works showed that altering walking sounds leads people perceiving themselves as thinner/lighter, happier and walking more dynamically. While this novel approach shows potential for physical activity, it raises critical questions impacting technology design. We ran two studies in the context of exertion (gymstep, stairs-climbing) to investigate how individual factors impact the effect of sound and the duration of the aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…The main contributions of our work are 1) our wearable device, SoniBand, which brings early prototypes (e.g., [18,41]) to a compact version to be used in ubiquitous environments, and includes a new sonification (Tone); 2) qualitative insights on how the body perception and PA was affected by different metaphorical sounds for participants in two different populations; and 3) a set of design considerations regarding particular sound qualities and characteristics to inform future research on metaphorical sonifications. These contribute to the body of work on sensory feedback, and in particular movement sonification [18,25,37,40,42] to alter body perception. The novelty of our work lies in the use of metaphorical sonifications to address negative/distorted body perceptions in the context of PA [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main contributions of our work are 1) our wearable device, SoniBand, which brings early prototypes (e.g., [18,41]) to a compact version to be used in ubiquitous environments, and includes a new sonification (Tone); 2) qualitative insights on how the body perception and PA was affected by different metaphorical sounds for participants in two different populations; and 3) a set of design considerations regarding particular sound qualities and characteristics to inform future research on metaphorical sonifications. These contribute to the body of work on sensory feedback, and in particular movement sonification [18,25,37,40,42] to alter body perception. The novelty of our work lies in the use of metaphorical sonifications to address negative/distorted body perceptions in the context of PA [3].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of one's perceived body may in turn have an effect on motor behavior and PA capabilities. For example, recent studies showed that altering the natural footsteps sounds produced by a person walking can make the person feel slimmer and lighter and adapt their walking behavior; if the person is exercising (i.e., using a gym step or climbing stairs), they will report that the exercise is easier, that they are less tired and that they can go faster [40,42]. While these works focused on altering the natural sounds produced by the body as a source of body alteration, an alternative approach to change body perception could be employing movement sonification.…”
Section: Movement Sonification To Affect Body Perceptionmentioning
confidence: 99%
See 3 more Smart Citations